Job Satisfaction of Managers in Cooperatives of Pokhara - Rakhal, Dhaneshwar (Tribhuvan University Journal, 2018)
This study tries to measure the job satisfaction level of managers working in saving and credit cooperative societies in Pokhara. It specially, ranks the managers' feelings about the general factors related to job satisfaction. It also considers gender, work experience and remuneration in relation to job satisfaction. It is based on the primary source of information and data collected through structured questionnaire. The data cover managers (office head) of 77 saving and credit cooperatives in Pokhara. Percentage, mean score, median, rank and chi-square test were used as analytical tools. The result of the study indicates that the five of the nine job satisfaction factors were under the satisfaction level. The result also points out that the female were more dissatisfied than male, and there was negative association between job experience and overall job satisfaction level and positive association between remuneration and overall job satisfaction.